Relevance of UNO in 21ST Centaury (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The UN's future is obscured by widespread disbelief and scepticism as it begins its second half-century. The sustainability of the UN in its current form is under doubt.The United Nations Organisation has started a study called The United Nations System in the 21st Century to investigate the most practical UN model. The study investigates what the UN might or ought to be in the twenty-first century using a dichotomous analytical model—the UN as Global Manager and Global Counsel—as a heuristic guide.United Nations, research programmes, international organisations, international institutions, and quantitative and qualitativeThe UN's problems are being investigated in two main stages: 1) a theoretical and empirical evaluation of the state of international institutions, and 2) the development of future policies, visions, and ideas. The three various viewpoints on the United Nations—as an actor, an arena, and a policy tool—form the basis of the framework for these research. Five core research groups and five yearly problem areas serve as the framework for research programmes based on these three models, which make up the project's main focus. The five main participants in international politics are examined by the groups: states, non-governmental organisations (NGOs), market forces, regional institutions, international organisations, and states. The primary research groups concentrate their efforts on the following five subject areas each year: 1) peace and security (1996); development (1997); environment (1998); human dignity (1999); and governance (2000).